Mechanical and microstructural characteristics of recycled aluminium matrix reinforced with rice husk ash - Olatunji P Abolusoro; Moshibudi Caroline Khoathane; Washington Washington (AIMS Materials Science)
This study used rice husk ash to reinforce recycled aluminium waste cans matrix through stir casting technique to produce a composite. The rice husk ash was added to the aluminium matrix in 0, 5, 10, 15, and 20 wt%. Mechanical and microstructural analyses were carried out on the composites. The tensile strength of the composite increases at 5 wt% addition of reinforcement and increases further to reach a maximum of 121.6 MPa at 10 wt% addition. The tensile value then dropped at 15 wt% and reduced further at the 20 wt% particulate addition. A similar trend was observed for the impact strength with the maximum value of 81.5 J occurring at 10 wt% addition before declining at the higher percentages of reinforcement. The hardness of the composites continues to increase as the percentage of the rice husk addition rises leading to the highest Brinell hardness number (BHN) of 74.5 occurring at the highest percentage of rice husk ash addition. The density of the composites decreases as the wt% addition of the reinforcement increases giving the lowest density value of 2.46 g/cm3 at 20 wt% addition. The microstructures exhibited uniformity in the dispersion of the reinforcement into the aluminium matrix, although little particulate agglomeration could be noticed at higher percentages of rice husk addition. This study provides a significant boost to the attainment of lightweight materials in the automobile and other allied industries. The improvement in the mechanical properties and the lower density of the composites attained in this study are vital factors considered in material selection and design for lightweight engineering applications.